CONTENT ANALYSIS OF THE NEW CUTTING EDGE INTERMEDIATE: ITS COMPATIBILITY WITH THE NEW SCHOOL BASED CURRICULUM SYSTEM - Indayani Indayani (Universitas Syiah Kuala, 2015)
It is not necessary to point out that no textbook is flawless. Each and every textbook has a number of potential strengths as well as limitations within its contents or its application in the teaching learning process. This research covers the analysis of several features of the New Cutting Edge Intermediate (NCEI) textbook and highlights a number of strong and weak points of this new textbook. In order to obtain the data for this study, the contents, layout and design, activities and tasks, grammar and skills presented in the textbook were scrutinized according to the School Based Curriculum (SBC) approach (Depdiknas, 2005), which is recently introduced into the Indonesian education system. More importantly, the distinctive approaches and principles underlying NCEI textbook design and also those of the SBC were analyzed to ascertain the extent of their compatibility.